Partial mixing and the formation of 13C pockets in AGB stars: effects on the s-process elements. Issue 1 (17th June 2017) - Buntain, J. F.; Doherty, C. L.; Lugaro, M.; Lattanzio, J. C.; Stancliffe, R. J.; Karakas, A. I.
Abstract: The production of the elements heavier than iron via slow neutron captures (the s process) is a main feature of the contribution of asymptotic giant branch (AGB) stars of low mass (<5 M⊙ ) to the chemistry of the cosmos. However, our understanding of the main neutron source, the 13 C(α, n) 16 O reaction, is still incomplete. It is commonly assumed that in AGB stars mixing beyond convective borders drives the formation of 13 C pockets . However, there is no agreement on the nature of such mixing and free parameters are present. By means of a parametric model, we investigate the impact of different mixing functions on the final s -process abundances in low-mass AGB models. Typically, changing the shape of the mixing function or the mass extent of the region affected by the mixing produce the same results. Variations in the relative abundance distribution of the three s -process peaks (Sr, Ba, and Pb) are generally within +/−0.2 dex, similar to the observational error bars. We conclude that other stellar uncertainties – the effect of rotation and of overshoot into the C–O core – play a more important role than the details of the mixing function. The exception is at low metallicity, where the Pb abundance is significantly affected. In relation to the composition observed in stardust silicon carbide grains from AGB stars, the models are relatively close to the data only when assuming the most extreme variation in the mixing profile.